2017
DOI: 10.1080/19440049.2017.1290829
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of the theoretical maximum daily intake of Sunset Yellow FCF by the Brazilian population

Abstract: This study estimated the theoretical maximum daily intake (TMDI) of Sunset Yellow (SY) synthetic food dye by the Brazilian population through food consumption data from the Household Budget Survey (HBS) of the Brazilian Institute of Geography and Statistics (IBGE, 2008/09). The study covered the population in urban and rural areas in the five regions of the country, and from different age groups, in order to verify if it were possible to exceed the acceptable daily intake (ADI) of SY, which is 4.0 mg kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“…It is interesting to note that the mean TMDI values increase as group age decreases for all food colours for the two HBS (except for Erythrosine for 2017/2018 where it was 0.1 mg/day for the three age groups). Feitosa et al (2017), in their study on the intake of the Sunset Yellow food dye by the Brazilian population using the 2008/2009 HBS, also observed that the younger the age group, the higher the intake.…”
Section: Intake By Age Groups: Adolescents Adults and Seniorsmentioning
confidence: 92%
See 1 more Smart Citation
“…It is interesting to note that the mean TMDI values increase as group age decreases for all food colours for the two HBS (except for Erythrosine for 2017/2018 where it was 0.1 mg/day for the three age groups). Feitosa et al (2017), in their study on the intake of the Sunset Yellow food dye by the Brazilian population using the 2008/2009 HBS, also observed that the younger the age group, the higher the intake.…”
Section: Intake By Age Groups: Adolescents Adults and Seniorsmentioning
confidence: 92%
“…This study was carried out following the methodology proposed by Feitosa et al (2017). Initially, a database was created for all processed food products whose labels indicated that they contained the artificial food colours Azorubine (INS 122), Ponceau 4R (INS 124), Erythrosine (INS 127), and Indigotine (INS 132).…”
Section: Methodsmentioning
confidence: 99%
“…The Budget method was used for Sunset Yellow FCF in the Brazilian (Feitosa et al, 2017) and tartrazine in the French (Elhkim et al, 2007) populations, and Tier 1 has been estimated for adults and children in the United States, United Kingdom (Tennant, 2008;EFSA, 2013EFSA, , 2014aEFSA, , 2014bEFSA, , 2015aEFSA, , 2015bEFSA, , 2015cTran et al, 2020), Italy (Fallico et al, 2011), and for Polish (Gajda-Wyrębek et al, 2017) and European (Huybrechts et al, 2010) children. More specific or refined steps are used when identifying safety concerns for exposure to the azo dyes evaluated in Tier 1 using the Budget method.…”
Section: Dietary Exposure Assessment and Risk Characterizationmentioning
confidence: 99%
“…In food processing, synthetic dyes are often added to color food due to their good stability in light, temperature, and pH and low price. , Sunset yellow (SY) is a typical artificial colorant that contains an azo group, which can not only achieve ideal colors but also improve the texture of foods when employed in fruit juices, cakes, sodas, cheese sauces, ice creams, canned fish, and spicy snacks . Given its large number of azo (NN) functional groups and an aromatic ring structure, the excessive intake of SY can potentially cause many adverse health effects, including allergies, eczema, migraine headaches, asthma, anxiety, and possibly cancer. , Hence, it is significant to perform quantitative studies of SY in food products.…”
Section: Introductionmentioning
confidence: 99%